Learning Speaking Using Guided Conversation Method to Increase Student Ability to Compose a Simple Dialoge - Syaifuddin, Muhammad Arif (ALSYSTECH Journal of Education Technology, 2024)
This article explores the use of innovative strategies in improving learners' ability to create simple dialog among Grade 8 learners at SMP Muhammadiyah 2 Taman Sidoarjo. The main focus of this research is to apply project-based learning model combined with guided conversation technique in learning the material of asking and giving opinion. Project-based learning as a learning model aims to stimulate the activeness, creativity of students in completing the learning. Learners are guided to create text in the form of a simple dialog with the theme of asking and giving opinion and then practiced with peers. By using guided conversation techniques, learners are guided intently to achieve learning objectives. Learning begins with the use of ice breaking relevant to the material, triggering questions, video footage, imitating conversations based on the text that has been provided until the practice of making conversations is a form of guidance to students. The research method applied in this study carries a combinative approach between project-based learning models with guided conversation techniques. The observation results showed a significant increase in students' active participation during the learning process. Students were more actively involved in group discussions, questions, and assignments. They are not only the recipients of information, but also the main actors in their own learning. This increased participation indicates that the models and techniques used are able to create a learning environment that stimulates more intensive student engagement. The conclusion we can draw is that this innovative strategy proves that the use of project-based learning model with guided conversation technique can be an effective step in improving learners' ability in the creation of speaking text in English language learning.